2011
DOI: 10.1002/jsfa.4628
|View full text |Cite
|
Sign up to set email alerts
|

Effects of germination on nutritional composition of waxy wheat

Abstract: Germinated waxy wheat had a better nutritional composition, such as higher dietary fibre, free amino acid and total phenolic compound contents, than ungerminated waxy wheat. Therefore germinated waxy wheat should be used to improve the nutritional quality of cereal-based products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
80
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(99 citation statements)
references
References 23 publications
14
80
1
4
Order By: Relevance
“…The different results observed were due to the different wheat varieties and the different germination methods used in each research. The wheats containing high amount of dietary fiber such as highamylose wheat or waxy wheat and germination temperature of 30°C are considered to be suitable for producing higher amounts of total dietary fiber and soluble dietary fiber in germinated wheats (Hung et al 2012;Koehler et al 2007). The significant increase in levels of soluble dietary fiber in this study may have potential nutritional benefits because soluble dietary fibre consumption was found to significantly lower blood cholesterol and help stabilize blood glucose levels (Anderson et al 1990;Brown et al 1999).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The different results observed were due to the different wheat varieties and the different germination methods used in each research. The wheats containing high amount of dietary fiber such as highamylose wheat or waxy wheat and germination temperature of 30°C are considered to be suitable for producing higher amounts of total dietary fiber and soluble dietary fiber in germinated wheats (Hung et al 2012;Koehler et al 2007). The significant increase in levels of soluble dietary fiber in this study may have potential nutritional benefits because soluble dietary fibre consumption was found to significantly lower blood cholesterol and help stabilize blood glucose levels (Anderson et al 1990;Brown et al 1999).…”
Section: Resultsmentioning
confidence: 99%
“…Tkachuk (1979) reported that the free amino acid content after 122 h of germination at 10, 16.5 and 25°C was respectively 4×, 10× and 7× that of ungerminated wheat. An increase in levels of ash and dietary fiber was clearly observed for the 48 h-germinated waxy wheat in the report of Hung et al (2012). Free phenolic compounds including ferulic acid, vanillic acid and syringic acid as well as total phenolic compounds and antioxidant capacity of germinated wheat significantly increased as compared with ungerminated wheat (Hung et al 2011(Hung et al , 2012.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations